The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1590/s0034-71671990000100016
|View full text |Cite
|
Sign up to set email alerts
|

Própolis: cicatrizante e antibiótico natural

Abstract: RESUMO -No presente trabalho os autores descrevem os resultados obtidos com o uso da Própolis, em 10 pacientes, com idade entre 22 e 57 anos, portado res de úlceras crônicas de membros inferiores de dife rentes etiologias. Analisam os resultados obtidos no que diz respeito a facilidade de seu uso" controle de in fecção local e avaliação do processo de cicatrização.ABSTRACT -In this study the authors describe the results obtained with Propolis or bee glue in 10 pacients (1 7 to 57 years old) suffe ring from cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
5

Year Published

1995
1995
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 1 publication
0
6
0
5
Order By: Relevance
“…Bernardo et al (1) ; Quintana (13) Clinical -Antimicrobial action -Therapeutic action in wound healing…”
Section: Thematic Focus Approachmentioning
confidence: 99%
See 3 more Smart Citations
“…Bernardo et al (1) ; Quintana (13) Clinical -Antimicrobial action -Therapeutic action in wound healing…”
Section: Thematic Focus Approachmentioning
confidence: 99%
“…Martinez Garcia et al (14) ;Duailibe et al (15) Clinical -Antimicrobial action Azevedo et al (4) ;Santos et al (11) ; Lofuto et al (35) Clinical -Therapeutic action in wound healing Peruchi et al (2) ;Park et al (3) ;Vargas et al (5) ; Fernandes Júnior et al (6) ; Silva et al (7) ;Sforcin et al (8) ; Sforcin et al (9) ;Oliveira et al (10) ; Auricchio et al (35) ; Fernandes Júnior et al (17) ;Machado et al (18) ;Longhini et al (19) ;Sawaya et al (20) ;Fernandes et al (21) ;Fernandes Júnior et al ( 22) ; Muli et al (23) ;Gebara et al (24) ;Fernandes Júnior et al (25) ;Bianchini et al (26) ;Gonçales et al (27) ;Dantas et al (28) ; Ayres et al (29) ;Orsi et al (30) ;Orsi et al (31) ;Sforcin et al (32) ;Sforcin et al (33) ;Orsi et al (34) ; Fernandes Júnior et al (36) ;Fernandes et al (37) ; Araújo et al (38) Experimental -Antimicrobial action Rahal et al (16) Experimental -Therapeutic action in wound healing (1) . Another study, which used propolis ointment on 22 chronic wounds, of which 11 were venous ulcers, seven pressure ulcers, two diabetic ulcers, and two post-trauma injuries, found that necrotic tissue was present in 14 (8.2%) during tissue assessment process.…”
Section: Thematic Focus Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…Em vista dessas deficiências, a procura por medicamentos alternativos vem crescendo, na intenção do controle de doenças (BERNARDO, et al, 1990). Uma alternativa natural utilizada em endodontia é a Própolis por possuir propriedades bactericida, analgésica, antiviral, anti-carcinogênica, antiinflamatória (MANARA, 1999).…”
Section: Lista De Tabelasunclassified